2016
DOI: 10.1007/s12160-016-9838-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Trauma Exposure and Pain-Related Outcomes Among People with Chronic Low Back Pain: Moderated Mediation by Thought Suppression and Social Constraints

Abstract: Background Research links people’s lifetime frequency of traumatic events to chronic pain. Attempts to suppress intrusive thoughts about trauma can paradoxically increase rumination, distress, and pain. Moreover, trauma-exposed individuals may experience social constraints against disclosure about their trauma, which might amplify thought suppression’s effect on pain. Purpose This study extends previous research on chronic pain by examining thought suppression and social constraints as mechanisms through whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
1
10
0
1
Order By: Relevance
“…Regarding the functionality of ER in LBP, pain‐related thought suppression (PTS) was associated with higher disability, which is in accordance to previous studies in (sub)acute (Hasenbring, Hallner, Klasen, et al, ; Held et al, ) and chronic LBP (Pegram et al, ; Scholich et al, ). Experimental research suggests that pain‐related thought suppression results in thought intrusions and increases of the very painful sensations that were sought to be suppressed (Cioffi & Holloway, ; Sullivan et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding the functionality of ER in LBP, pain‐related thought suppression (PTS) was associated with higher disability, which is in accordance to previous studies in (sub)acute (Hasenbring, Hallner, Klasen, et al, ; Held et al, ) and chronic LBP (Pegram et al, ; Scholich et al, ). Experimental research suggests that pain‐related thought suppression results in thought intrusions and increases of the very painful sensations that were sought to be suppressed (Cioffi & Holloway, ; Sullivan et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…To this end, pain‐related thought suppression may serve to enable pain persistence, also known as overactivity, eventually resulting in overuse (Andrews et al, ; Hasenbring & Verbunt, ) and depressive mood (Hülsebusch, Hasenbring, & Rusu, ; Konietzny et al, ) (Figure ). Thus, endurance‐related responses (ER) are, like FAR, associated with disability (Andrews et al, ; Hasenbring, Hallner, Klasen, et al, ; Held et al, ; Pegram, Lumley, Jasinski, & Burns, ; Scholich, Hallner, Wittenberg, Hasenbring, & Rusu, ) and pain intensity (Hasenbring, Marienfeld, Kuhlendahl, & Soyka, ; Held et al, ; Pegram et al, ; Scholich et al, ), (see Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of patients with chronic pain also suffer with multiple psychological conditions, specifically depression and anxiety (12,110,567,. Numerous investigators have shown the relationship between psychological and emotional distress and increased levels of pain-related disability, chronicity, and use of health care services (587)(588)(589)(590)(591)593,595,(600)(601)(602). Symptoms of depression and anxiety also have been studied regarding long-term physical health outcomes in rheumatoid arthritis (596), showing that baseline and persistent symptoms of depression and anxiety were associated with poorer health outcomes over time, as well as reduced treatment response.…”
Section: Psychological Evaluationmentioning
confidence: 99%
“…Thought suppression was shown to moderate the relationship between depression and pain in acute and subacute [161] and in chronic back pain [162]. In chronic low back pain, thought suppression is further seen as a risk factor for poorer pain outcomes, heightened pain severity, increased pain interference, and depressive symptoms [163]. Experiencing pain, many patients show a suppression reaction, followed by an emergence of different negative consequences, such as distress, depressive moods, and increased pain [137,147,158,164,165].…”
Section: A C C E P T E Dmentioning
confidence: 99%